Issues, challenges and opportunities in accessing primary health services in tribal-rural setting in India: a decadal view - Kumar, Vivek; Kumar, Dinesh (International Journal Of Community Medicine And Public Health, 2022)
Even after 75 years of independence, the country’s most underprivileged tribal population is still far from getting health benefits. Tribals in India have poor health and present a bleak picture in terms of social development metrics, especially health. From this perspective, this paper is intended to identify the problems and existing challenges faced by tribal communities in accessing health care from primary health care settings. Exploring the observations based on reviewed scholarly articles published between 2012 and 2022 from databases like PubMed and Google Scholar and in addition to several government reports and articles. These articles were selected and subsequently analyzed to extract specific outcomes. By applying the principle of the ’five A’ approach, the analysis revealed a significant shortfall in the service delivery of health wellness centers. It was implicit that despite the introduction of affirmative policies by the government, gaps still existed in the healthcare system at grass root level. Major gaps are lack of human resources, staff stereotyping indigenous population, and inadequate infrastructure; and high health costs due to out of pocket expenditure and informal payments were evident. The paper recommended both individual and community-level strategies to overcome the barriers of rural health services. More decentralized planning and cultural competency training are immediate measures for the inclusion of tribal-rural people in healthcare services. Further, we proposed developing a "Mangal Health Team’ which will coordinate between Health and wellness centre and villagers.